Solid–liquid equilibria of Sorel phases and Mg(OH)2 in the system Na-Mg-Cl-OH-H2O. Part II: Pitzer modeling - Freyer, Daniela; Pannach, Melanie; Voigt, Wolfgang (Frontiers in Nuclear Engineering, 2023)
For geochemical calculations of solubility equilibria between Sorel phases, Mg(OH)2 and oceanic salt solutions, the polythermal THEREDA data set (based on the HMW model at 25°C) was extended. With both models H + solution concentrations in equilibrium with Mg(OH)2(s) and 3-1-8 Sorel phase at 25°C can be calculated in good agreement. In contrast, the calculated OH -solution concentrations do not agree. Using the solubility constants (lg Ks) determined up to 60°C in Part I of this work, together with the available solubility isotherms up to 120°C, temperature functions for the 3-1-8 phase (25-100°C), 2-1-4 phase (60-120°C) and 9-1-4 phase (100-120°C) were derived. In order to accurately model the OH -solution concentrations, it was necessary to implement the solution species, Mg3(OH)4 2+ (∆R ° temperature function), in addition to MgOH + already contained in the previous model. Finally, fitting Pitzer mixing coefficients for both species now allows the calculation of solubility equilibria of Mg(OH)2(s) and the Sorel phases in agreement with the experimental data in the Mg-Cl-OH-H2O and Na-Mg-Cl-OH-H2O systems.